STUDI KASUS GAMBARAN PEMENUHAN KEBERSIHAN DIRI PADA ANAK DENGAN TUNANETRA DI SLB NEGERI 1 BANTUL - Yobileum Iskatri; Margareta Hesti Rahayu (Journal of Advanced Nursing and Health Sciences, 2021)
Personal hygiene is an action to maintain the cleanliness and health of a person for well-being, both physically and psychologically. According to the Indonesian Ministry of Health (2014), the number of blind people in Indonesia is 3,750,000 (1.5%) both blind and visually impaired. From the results of interviews with tutors, data obtained from 15 blind children, five of whom experienced personal hygiene disorders. This research design uses descriptive qualitative research with case study method. Data collection by observation dan interview with children and parent. The results of this study: Children take a bath 2 times a day and need help to do and the other self-care. There are no special tools and materials for personal hygiene. Conclusion: children routinely carry out personal hygiene, but they still need the help of others in fulfilling their personal hygiene needs.